Protective Effect of Ethanol Extract of Celery (Apium graveolens L) on Kidney Damage in Ischemia/ Reperfusion Injury Rats Model - Afifah Afifah; Khusnul Muflikhah; Viva Ratih Bening Ati; Rizki Maulana Tsani; Dairotul Khasanah; Watub Maulana (Molekul, 2019)
Ischemia/ reperfusion injury (IRI) is marked by the sudden decrease of blood supply to the kidney followed by restoration of blood flow. Ischemic acute kidney injury (AKI) is the leading cause of morbidity and mortality. Therefore, the prevention strategy for decreasing the damage due to IRI is required. Celery (Apium graveolens L) is often consumed as food. Celery has antioxidant and anti-inflammatory effects. This study aimed to investigate the protective effect of the celery on kidney damage in the kidney ischemia/ reperfusion injury rat model.  Twenty-five rats male, 2-3 months old Sprague Dawley were divided into 5 groups: Group 1  was sham operation, group 2 was ischemia/ reperfusion injury (IRI), group 3, 4, 5 were IRI and 250 mg/kgBW, 500 mg/kgBW, 1000 mg/kgBW of ethanol extract of celery respectively for 14 days before and 3 days after operation. Blood serum sample was taken 3 days after the operation for measuring urea, creatinine, superoxide dismuthase (SOD) and nitrite oxide (NO). Hematoxylin-eosin (HE) staining was utilized to examine kidney tubular injury score. Data were analyzed using One-way ANOVA (p<0,05). The ethanol extract of celery at dose 1000 mg/kgBW prevented the increase of urea, creatinine serum, kidney tubular injury score and prevented the decrease of SOD, NO in the kidney ischemia/ reperfusion injury rat model (p<0,05). In conclusion, the ethanol extract of celery has a protective effect on kidney damage in the ischemia/ reperfusion injury rat model.